Analisis Hasil Proyek dan Respon Siswa terhadap Kit STEAM Energi Terbarukan - Lintang Rahmayanti; Sentot Budi Rahardjo; Sukarmin (Jurnal Penelitian Pendidikan IPA, 2024)
Addressing global challenges requires a strong focus on environmental sustainability within educational institutions. This research aims to analyze the project outcome and student’s responses of Renewable Energy STEAM Kit. The study involved 31 students who participated in the learning project using Renewable Energy STEAM Kit. Data was collected through observation to assess the project outcome of learning activities, and survey & interview to gather student’s responses about their experiences from learning activities using Renewable Energy STEAM Kit. Data processing utilized descriptive quantitative methodologies to derive significant insights from the provided data. According to the result, 96.8% of students agreed and strongly agreed that the Renewable Energy STEAM Kit is easy to use, interest, flexible, benefit, and relevant. Only 3.2% of students that disagreed about that statement. The results of this study can be concluded that Renewable Energy STEAM Kit's success in being user-friendly, engaging, flexible, beneficial, and relevant to students' educational experiences and future aspirations.